The role of public administration in building a harmonious society : (ADB, 2006)
This book includes many parts: enlarging citizen participation and increasing autonomy of local government in achieving societal harmony, public administration strategies that help or hinder societal harmony, innovations in governance and public service to archieve a harmonious society, ...